The influence of psychopathology, personality, and marital interaction on the short-term course of major depression - Mundt, Christoph; Kronmüller, Klaus-Thomas; Backenstraß, Matthias; Reck, Corinna; Fiedler, Peter (Psychopathology, 1998)
By means of an aggregated variables design the domains of ‘psychopathology’, ‘personality’, and ‘social interaction’ were weighted according to their impact on the 2-year course of 50 patients with unipolar major depression. Preindex course ranked highest, asthenic personality second. Variables of social interaction disappeared in the second-order logistic regression. These findings fit in well with the recent literature. They are interpreted in terms of habituation processes and residual personality changes which lower the vulnerability threshold for relapse and unfavorable course. As a consequence of this conclusion early relapse prevention would be most important.
Gesehen am 22.01.2021